Participatory epizootiology research of settled pastoralists in Igangan grazing reserve, Southern guinea agro-pastoral zone, Oyo State, Nigeria: first report (2011)
Participatory Epizootiology Research of a Fulani agro- pastoralist settlement scheme, the Igangan Grazing Reserve, Oyo Stole, Southwest Nigeria between 2007 and dole, is ongoing under o University of Ibadan, Nigeria Senole Research Grant Program. The objective is to identify and rank the expressed epizootiological and livestock health problems, as well as the socio-economic needs related to livestock-keeping, of the pastoralists in the study area. After obtaining approval from the reserve authorities (the Oyo State Government), on initial field assessment, two interactive focus group discussions meetings and a second physical field visit took place between December 2007 and June 2009. Respondents included the traditional Fulani grazing reserve head, who has been o settler on the reserve for forty (40) years, his educated first son and heir apparent, as well as fifteen (IS) other settler leaders/elders. There were between twenty-seven (27) and forty-seven (47) permanent settlers, depending on the season of the year, with cattle holding of SO - 600 per household. Settlers were mainly Fulani pastoralists. Problems highlighted by settlers included inadequate space for settler families, crop former/pastoralist skirmishes, und non-availability of feed oil year round and absence of veterinary / animal core services. Expressed needs were for basic veterinary training in animal core (and not just drug usage), disease prevention and management practices and veterinary extension education. Four (4) major reserve diseases identified were (harbo (Foot and- Mouth Disease). Samore (Tryponosomosis), Cheren/Unto (Contagious Bovine Pleuro pneumonia) and Wolah (Skin eruptions).